2014
DOI: 10.1177/1082013214559310
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of functional properties and color changes of corn extrudates enriched with broccoli or olive paste

Abstract: Following the tendency of replacing common food snacks with healthier food products, extruded snacks with corn flour and broccoli (4-10%) or olive paste (4-8%) were investigated in this study. The effect of material characteristics, including feed moisture content (14-19%), and broccoli or olive paste concentration, and extrusion conditions, including screw speed (150-250 r/min), and extrusion temperature (140-180 ℃), on the functional properties (water absorption index, water solubility index, and oil absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 82 publications
(115 reference statements)
3
6
0
1
Order By: Relevance
“…The WAI range reported by other authors depended on raw materials used, the type of extruder and processing conditions, and varied from 4.5 to 6.6 g•g -1 for gluten-free extrudates based on rice flour and from 3.6 to 5.6 g•g -1 for fiber-enriched extrudates (Stojceska et al, 2010) and from 5.3 to 6.2 g•g -1 for sorghum-bambara groundnut extrudates (Gbenyi et al, 2016). Similar results, varying from 5.6 to 6.4 g•g -1 were reported for WAI of corn extrudates with added broccoli and olive paste (Bisharat et al, 2015), but a WAI almost 50% lower was observed for extruded instant rice-soybean or rice-mung bean porridge, varying from 3.21 to 2.77 g•g -1 , which decreased when the amount of legumes was increased (Mayachiew et al, 2015).…”
Section: Physical Properties Of Corn-rice Instant Gruelssupporting
confidence: 81%
See 2 more Smart Citations
“…The WAI range reported by other authors depended on raw materials used, the type of extruder and processing conditions, and varied from 4.5 to 6.6 g•g -1 for gluten-free extrudates based on rice flour and from 3.6 to 5.6 g•g -1 for fiber-enriched extrudates (Stojceska et al, 2010) and from 5.3 to 6.2 g•g -1 for sorghum-bambara groundnut extrudates (Gbenyi et al, 2016). Similar results, varying from 5.6 to 6.4 g•g -1 were reported for WAI of corn extrudates with added broccoli and olive paste (Bisharat et al, 2015), but a WAI almost 50% lower was observed for extruded instant rice-soybean or rice-mung bean porridge, varying from 3.21 to 2.77 g•g -1 , which decreased when the amount of legumes was increased (Mayachiew et al, 2015).…”
Section: Physical Properties Of Corn-rice Instant Gruelssupporting
confidence: 81%
“…WSI values of extruded instant gruels ranged from 7 to 24% for mixtures containing 25% rice, and from 8 to 18% for recipes based on 50:50 corn-rice mixtures. The WSI of corn-rice extruded crisp bread was 24.6%, as reported by Gondek et al (2013), or varied from 10.9 to 18.7% for corn extrudates with broccoli or olive paste added (Bisharat et al, 2015). Based on these results, it can be concluded that increasing moisture content of raw materials up to 18% resulted in a significant decrease in WSI values (Fig.…”
Section: Physical Properties Of Corn-rice Instant Gruelssupporting
confidence: 77%
See 1 more Smart Citation
“…Color is an attribute that has a high influence on the acceptability of foods by consumers. Thermal processes can produce changes in color parameters by the loss or degradation of pigments and the generation of colored compounds due to chemical reactions, such as Maillard reactions and caramelization (Bisharat, Katsavou, Panagiotou, Krokida, & Maroulis, ). The color L* parameter indicates the brightness of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Niższe wartości WSI typowe są dla produktów owsianych, jęczmiennych [Rzedzicki i Wirkijowska 2008] oraz wszystkich tych produktów uzyskanych na bazie zbóż, które przed spożyciem wymagają obróbki termicznej jak na przykład makarony. Dużo wyższe wartości WSI, przekraczające nawet 50% obserwuje się w wielu wysoko przetworzonych przekąskach zbożowych [Rzedzicki i Wirkijowska 2008, Bisharat i in. 2015.…”
Section: Wyniki I Dyskusjaunclassified